Exploring remote earthquake triggering potential across EarthScopes' Transportable Array through frequency domain array visualization. Issue 12 (11th December 2014) - Linville, Lisa; Pankow, Kristine; Kilb, Debi; Velasco, Aaron
Abstract To better understand earthquake source processes involved in dynamically triggering remote aftershocks, we use data from the EarthScope Transportable Array (TA) that provide uniform station sampling, similar recording capabilities, large spatial coverage, and, in many cases, repeat sampling at each site. To avoid spurious detections, which are an inevitable part of automated time domain amplitude threshold detection methods, we develop a frequency domain earthquake detection algorithm that identifies coherent signal patterns through array visualization. This method is tractable for large data sets, ensures robust catalogs, and delivers higher resolution observations than what are available in current catalogs. We explore seismicity rate changes local to the TA stations following 18 global main shocks (M ≥ 7) that generate median peak dynamic stress amplitudes of 0.001–0.028 MPa across the array. From these main shocks, we find no evidence of prolific or widespread remote dynamic triggering in the continental U.S. within the main shock's wave train or following main shock stress transients within 2 days. However, limited evidence for rate increases exist in localized source regions. These results suggest that for these data, prolific, remote earthquake triggering is a rare phenomenon throughout a wide range of observable magnitudes. We further conclude that within the lower range of previously reported triggering thresholds, surface wave amplitude does not correlate well with observed cases of dynamic triggering. We propose that other characteristics of the triggering wavefield, in addition to specific conditions at the site, will drive the occurrence of triggering at these amplitudes.